Legal Responsibility for Mystery Box Sale and Purchase Transactions in E-Commerce - Marcella, Grace; Dirkareshza, Rianda (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Mystery box is a product whose sales concept does not explain clearly and completely the information on the goods being traded. The purpose of this study is to find out how the validity and legal accountability of mystery box buying and selling transactions in e-commerce. The research method used in this study is to use normative legal research methods, considering the object/focus of this research study is a product of statutory regulations. The results of the study show that related to mystery box buying and selling transactions, business actors in carrying out these activities do not carry out the principle of good faith so that they are not in accordance with Article 45 paragraph 2 of Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions. In the event that the consumer is not provided with complete and clear information regarding the mystery box product purchased by the consumer, it is not in accordance with Article 4 of the PK Law, Article 7 of the PK Law, Article 8 of the PK Law, Article 18 of the PK Law, Article 48 and Article 50 paragraph (1 ) Government Regulation Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions, for violations of Article 8 of the PK Law according to Article 62 paragraph (1) of the PK Law, can be subject to imprisonment and fines.